Pendampingan Penggunaan Sistem Informasi CekRek bagi Guru dan Orang Tua di SLB Satria Galdin - Tajimalela, Akwan Cakra; Santosa, Krisna; Hasanah, Anisa Rohmah; Salsabila, Indri; Nurazizah, Tiara Nazwa; Lestari, Triana (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The process of disseminating assessment results is a problem that must be considered because the dissemination of assessment results is still conventional. This problem is also experienced by several SLBs, especially SLB Satria Galdin. This community service program aims to optimize the dissemination of information on the results of assessments of students with autism using the CekRek information system, an innovation by the Helov PKM team. This information system contains the digitalization of the M-CHART-R/F assessment and provides recommendations for daily activities for students with autism. The method used in the community service activity was a workshop held in July 2024 and attended by teachers and parents of students at SLB Satria Galdin as partners of the Helov PKM team. This community service program produced a CekRek information system that can help parents monitor their children's development and assessments in real time. In addition, it also produces a guidebook for partners regarding the CekRek information system. This activity was socialized in the SLB Satria Galdin area and social media. Evaluation of the questionnaire activity using Google Form and getting a positive response.